Antibiotics for acne vulgaris: using instagram to seek insight into the patient perspective. (17th February 2021) - Reddy, Pooja S.; DeBord, Logan C.; Gupta, Rohit; Kapadia, Paarth; Mohanty, Alina; Dao, Harry
Abstract: Objectives: Monitoring of public social media posts is an underutilized method to understand patients' perspectives regarding their condition and treatment. We investigated information shared by Instagram users of oral and topical antibiotics for treatment of acne vulgaris. Material and methods: We performed a retrospective observational study of public Instagram posts assigned common hashtags to denote the use of antibiotics therapy for acne over nearly eight years. Results: Dissatisfaction was more prevalent among users of oral antibiotics (25.6%) compared to users of topical antibiotics (9.8%), and negative tone among this group was most commonly due to lack of improvement in skin appearance. Reported side effects paralleled known side effects for oral and topical antibiotics. Conclusions: Instagram may have utility in elucidating patient behavior and attitudes. Dermatologists should increase their social media presence in order to disqualify any incorrect information endorsed in 'popular' or commonly viewed posts.